Disproportionality analysis of oesophageal toxicity associated with oral bisphosphonates using the FAERS database (2004–2023) - Chen, Lin; Dai, Zhicheng; Song, Huangrong; Zhang, Jiafeng; Li, Tuo (Frontiers in Pharmacology, 2024)
Background: This study analyzed the FDA's Adverse Event Reporting System (FAERS) data to investigate the correlation between oral bisphosphonates (BPs) and oesophageal adverse events (AEs).We systematically extracted data on adverse reactions to oral alendronate, risedronate, and ibandronate from the FAERS database, covering the period from the 2004 Q1 to the 2023 Q4. The role_code of AEs mainly includes primary suspect (PS), secondary suspect (SS), concomitant (C), and interaction (I).This study targeted reports with a role_code of 'PS.' According to the FDA deduplication rule, the latest FDA_DT is selected when the CASEID is the same, and the higher PRIMARYID is selected when the CASEID and FDA_DT are the same. Our analysis leveraged four statistical methods, including the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma poisson shrinker (MGPS), to assess the relationship between oral bisphosphonates and oesophageal AEs. The Kaplan-Meier method was utilized to evaluate the cumulative incidence of oesophageal toxicity, while the log-rank test examined the temporal onset profiles of these toxicities. Additionally, the Pearson chi-squared test was employed to identify any significant differences in mortality and hospitalization rates associated with the oesophageal AEs caused by these medications.The FAERS database had 41,590 AE reports for oral BPs, with 3,497 (8.41%) related to oesophageal AEs. Our findings indicate that oral BPs are disproportionately associated with an increased incidence of gastrointestinal system AEs at the system organ class (SOC) level. The adverse events identified at the preferred terms (PTs) level encompassed conditions such as gastroesophageal reflux disease, oesophagitis, and oesophageal pain. A significant divergence in the cumulative incidence of oesophageal AEs was observed among patients treated with the three different oral bisphosphonates, as confirmed by the log-rank test (P < 0.0001). Hospitalization rates varied significantly among patients receiving different BPs (P < 0.05), but no significant difference in mortality rates was found.The study establishes a significant link between oral BPs and oesophageal toxicity, highlighting the need for further research into the mechanisms of BP-induced oesophageal toxicity and potential preventive measures.